2021
DOI: 10.1186/s12876-021-01758-w
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive diet in a patient with irritable bowel syndrome leading to Wernicke encephalopathy

Abstract: Background We present a case of a woman with a past medical history of irritable bowel syndrome (IBS) and anxiety, who presents with ophthalmoplegia, ataxia and memory loss, characteristic of Wernicke encephalopathy. Case presentation A 64-year-old woman presented with double vision, unsteady gait and memory loss. These symptoms began after 3 months on an unfortified restricted diet, which she initiated to alleviate IBS symptoms. Magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that MRI has a high specificity but low sensitivity for WE [ 14 , 16 ]. However, a large number of researchers believe that MRI is a powerful and reliable tool that should be used to support the diagnosis of acute WE in both alcoholic and and nonalcoholic individuals [ 5 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that MRI has a high specificity but low sensitivity for WE [ 14 , 16 ]. However, a large number of researchers believe that MRI is a powerful and reliable tool that should be used to support the diagnosis of acute WE in both alcoholic and and nonalcoholic individuals [ 5 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%